Strengthening Strategies for RC Beams with Vertical Openings Using Embedded Steel Bars - Ghani, Haider Abedulrudha; Izzet, Amer F. (Engineering, Technology & Applied Science Research, 2025)
Circular or rectangular openings are often incorporated into Reinforced Concrete (RC) beams to accommodate the service requirements of the buildings, such as telephone lines, sewage systems, and water supply pipes. These concrete beams need to be strengthened and repaired, as the presence of openings reduces their stiffness, which results in severe deformations and a significant redistribution of load. An experimental study of the impact of vertical openings on the structural behavior of simply supported RC beams is presented in this research. Five RC beams were tested as part of the experiment. The beams were split into two groups based on the vertical opening’s shape. One of the beams was kept as a reference beam (without any openings). One beam in each group was internally strengthened with reinforcing steel rebar, whereas the other was not. The experimental findings demonstrated that, for all studied specimens, independent of the opening shape, the development of openings within the RC beams resulted in an increase in the service midspan deflection and a decrease in the ultimate load carrying capacity. The maximum decrease in the ultimate load was approximately 27.7% for the un-strengthened specimens compared to the reference specimen. In contrast, compared to the beams without reinforcement, the rebar strengthening was successful in enhancing the ultimate load and reducing the service midspan deflection by approximately 19% and 29%, respectively. Additionally, the experimental results demonstrated that, when compared to a reference beam, the strain values of the top and bottom steel reinforcement at the mid-span increased at the same applied load level (at service load). However, when additional steel reinforcement was used to strengthen the beam around the vertical openings, the strain in both the top and bottom rebar decreased.